IMPLEMENTATION OF DIFFERENTIATED LEARNING TO IMPROVE EDUCATIONAL SCIENCE AND CHARACTER LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Ni Putu Eni Astuti; I Wayan Suastra; Ida Bagus Arnyana; I Komang Nada Kusuma (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This research is qualitative and involves 21 fourth-grade students of SD Negeri 6 Pempatan. Based on interviews with the class IV homeroom teacher, the minimum competency assessment (AKM) for students' literacy and numeracy requires special intervention, resulting in very low learning outcomes, particularly in science subjects. This study aims to improve students’ learning outcomes in the science topic of plant body parts. The research implements differentiated learning that accommodates three learning styles: visual, auditory, and kinesthetic. Data were collected through observations and interviews and analyzed using qualitative descriptive analysis. The results indicate that the learning outcomes of fourth-grade students at SD Negeri 6 Pempatan improved, as evidenced by the increase in scores between learning 1 and learning 2. Moreover, the findings highlight that student-centered learning activities enhance the learning process, providing meaningful experiences and enabling students to develop values from science learning as well as Pancasila student profiles, thereby strengthening character education.